Comparison of energy consumption and carbon emissions from clinker and recycled cement production. (15th July 2021) - Sousa, Vitor; Bogas, José Alexandre
Abstract: The cement industry is presently facing the demanding challenge of reducing its large amount of carbon emissions in order to meet the targets set to fight climate changes. One recent, and very promising, approach to reduce the carbon footprint is the production of more eco-efficient recycled cement from cement-based waste materials. This study aims at comparing the difference in terms of energy consumption and carbon dioxide emissions between recycled cement and conventional clinker production. In a conservative scenario, the estimated carbon dioxide emissions from recycling cement was as low as 58%–74% of the clinker production. From the sensibility analysis, it was found that the most influencing factors for the carbon emissions from the recycled cement production are: i) the waste cement water content; ii) the fraction of cement paste on waste material; and iii) the dryer energy intensity. The main drawback of the recycled cement production process is the pretreatment stage related with washing and drying of waste materials. The carbon dioxide emissions from recycled cement production can be potentially reduced to only 13% of the emissions from clinker production, if these pretreatment stages are avoided by developing a dry process. Highlights: The production of recycled cement tackles the cement industry and construction and demolition waste management challenges. The CO2 emissions from producing recycled cement are only 58%–74% of the clinker production. A subproduct of the recycled cement production is fine recycled aggregates with low cement paste content. Developing a dry production process for recycled cement will reduce the CO2 emissions to only 13% of the clinker.